Upaya Kepala Sekolah dalam Meningkatkan Profesionalisme Guru melalui Kegiatan Peer Teaching di Madrasah Ibtidaiyah Negeri 12 Kota Medan - Hasnah Siregar (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
To increase teacher professionalism in MIN 12 Medan City an action was carried out using the teaching model per teaching. This research was conducted in MIN 12 Medan City with the research object of 38 teachers. The research method used in this study is a school action research using two cycles carried out in September 2018 to December 2018. Based on the results of the study obtained that by using a model of peer teaching activities for teachers of MIN 12 Medan City can increase the professionalism of MIN 12 Medan teachers . This is shown based on the results of the study at the time of pre-cycle there were 16 teachers or 42%, after the learning model per teaching in the first cycle there was an increase to 28 people (73%), then continued with cycle 2 there was an increase to 36 people (94 %). This proves an increase in teacher discipline after the principal uses the learning model per teaching. The implementation of classroom supervision carried out by the principal through the learning model approach per teaching is proven to improve the quality of learning because this happens because the supervised teacher does not feel awkward / afraid in carrying out learning. In this supervision activity the principal acts more to guide and assist supervised teachers.